Giant Aggressive Extraocular Sebaceous Carcinoma: A Case Report - Liu F; Qi F; Zhang X; Cao M (Dove Medical Press, 2021)
Fang Liu, Fei Qi, Xiuying Zhang, Mei Cao Department of Dermatology, Beijing Chaoyang Hospital, Capital Medical University, Beijing, People's Republic of ChinaCorrespondence: Fang LiuDepartment of Dermatology, Beijing Chaoyang Hospital, Capital Medical University, Beijing, People's Republic of ChinaTel +86-10-85231688Fax +86-10-85231217Email roseliufang@qq.comAbstract: Sebaceous carcinoma (SC) is a rare, aggressive malignancy. Most lesions occur in the periocular region, with few cases presenting with extraocular lesions. Here, we report a case of an 89-year-old woman with a 3-month history of a rapidly growing giant extraocular SC. The diagnosis was based on skin biopsy findings. We advised the patient to undergo surgical excision of the carcinoma. However, the patient and her family rejected our proposed surgical treatment, opting for topical traditional Chinese medicine as alternative treatment. The patient subsequently died of unknown causes at home, four months after the first visit. This case of treatment failure emphasizes the importance of early detection and treatment for these aggressive tumors.Keywords: sebaceous carcinoma, extraocular, skin neoplasms, malignancy, Muir-Torre syndrome